(untitled) (Al-Academy, 2025)
Women’s traditional clothing in Mecca has garnered the attention of researchers due to its unique distinction. It continues to hold its place among the people of Hijaz, who wear it on special occasions. The study aims to use Meccan heritage clothing as a source of inspiration for designing modern women’s fashion through artificial intelligence. The significance of the study lies in promoting Meccan cultural identity and employing AI applications to innovate designs that are fashionable and marketable. The historical method was used to describe past events, along with an applied methodology where nine clothing pieces inspired by Meccan heritage were designed, accompanied by 27 varied designs including dresses, skirts, and blouses. The researcher concluded that cultural identity can be enhanced through fashion and recommended future studies on AI in fashion design to develop modern designs that cater to all tastes, as well as to produce contemporary women’s clothing for sale during Hajj and Umrah seasons.